Association study of CFH Y402H functional variant with genetic susceptibility to nicotine dependence and schizophrenia in Turkish population - Sever, Ülgen; Nursal, Ayşe Feyda; Çetinay Aydın, Pınar; Uysal, Mehmet Ali; Özdilli, Kürşat; Pehlivan, Mustafa; Aydın, Nur Gökçe; Pehlivan, Sacide (American Society for Cell Biology, 2018)
[Abstract Not Available]
Keywords: Schizophrenia; Nicotine Dependence; Complement Factor H; Y402H Variant